(untitled) (European Journal of Marketing and Economics, 2023)
The concept of mutual funds in India dates back to the year 1963. The era between 1963 and 1987 marked the existence of only one mutual fund Company in India, namely the Unit Trust of India (UTI), with Rs. 67 billion assets under management (AUM). Few other mutual fund companies entered the mutual fund market later on. The private sector funds started penetrating the fund families during 1993. Kothari Pioneer was the first private sector mutual fund company in India which has now merged with Franklin Templeton. By the end of 1993, the total AUM of the industry was Rs. 470. 04 billion. Just after ten years with private sector penetration, the total assets rose up to Rs. 1218. 05 billion and till 2004, it reached the height of 1540 billion. The total AUM of the mutual fund industry has risen up to 14000 billion in April, 2016. Today there are 43 mutual funds in India offering a number of schemes suited to the needs of different type of customers. It has been noticed that the private sector mutual funds have been taking more risks and have also been able to gain higher returns on an average. This paper tries to highlight the comparative performance of public and private sector mutual funds and also throw light on the scope of the existing potential of the fund market in the face of traditional risk aversion of the investors and huge rise in financial assets.